Tackling the Economic Challenges of COVID-19: A Look at the Federal Reserve System: History and Present Day - Dutta, Amitabh S.; Kulkarni, Kishore; Lai, Kun Peng (Finance & Economics Review, 2022)
In this paper, we take a look at some of the measures taken by the central bank of the United States viz. the Federal Reserve System, to help businesses, both small and large, to weather the unprecedented economic challenges faced by managers and owners of businesses to survive through the crisis of shutdowns, lost sales, unemployment, and illness. One such step taken by the Federal Reserve was to lower the discount rate, the rate at which Federal Reserve gives loans (Discounts and Advances) to U.S. financial institutions. It may be taken as a standard response to economic slowdowns by central banks around the globe, but Federal Reserve's action has more significant effects than any other central bank. While there is no "one size fits all" economic measure that works in all countries in the wake of the pandemic, we believe that knowing and discussing what one central bank did – can lead to bankers, academics, politicians, business managers and owners from different countries share their experiences and tailor proposals and plans to fit the needs of an individual country. In this spirit, this proposed paper is an endeavor to examine the role of monetary policy in averting the forces of the pandemic. The paper is divided into three sections. Section 1 talks about the structure of the Federal Reserve System, surveys some historical behavior and examines the decision-making process in the system. Section 2 discusses the economic impacts of coronavirus on all economic aspects but focuses more on the monetary structure of the US economy. Section 3 makes the argument that expansionary monetary policy was a tremendous necessity of the time, but overdoing its activity in the same direction may bring back the threat of inflation. Summary and conclusion follow Section 3.